Exploring Holiday Market Anomaly: Evidence from International security Indexes - Enow, Samuel Tabot (Dinasti International Journal of Economics, Finance & Accounting, 2023)
Research on financial market anomalies has always been a subject of fascination for researchers and investors alike. Over the years, numerous anomalies and patterns have been identified, one of which was the holiday market anomaly which refers to the recurring and abnormal behavior observed in the stock markets during the holiday season. It is a phenomenon that has captured the attention of scholars and investors due to its potential implications for investment strategies and market efficiency. The aim of this study was to ascertain or rebuff the concept using the most recent data. Accordingly, a t-test statistics was used to analyze data from a sample of six financial markets from June 12, 2018, to June 12, 2023. The findings revealed no evidence of the existence of the holiday market anomaly, at least for the most recent 5 years. A possible reason for the extinction may have been the introduction of new financial products and the spread of numerous investment strategies. Hence, long-term investors are encouraged to prioritize fundamental analysis and a disciplined investment approach, recognizing the limitations and potential risks associated with trading based on the holiday market anomaly.